Peran Pembelajaran Daring pada Mata Pelajaran Pendidikan Agama Buddha dalam Menghadapi New Normal di SMK Metta Maitreya Pekanbaru - Sonika Sonika (Jurnal Maitreyawira, 2022)
ABSTRACT The study focuses on "The Role of Online Learning In New Normal at SMK Metta Maitreya Pekanbaru", Involved by principal, Head of MGMP Pekanbaru, the buddhist teacher and students of SMK metta maitreya. Data collection with observation, interviews, documentation, and triangulation. The interactive data analysis technique (miles and huberman,1994: 12), through data reduction, data presentation, and deduction/verification. Data validity with the concept of validation of triangulation and a member of the check. The results of the study were revealed: First;The online learning of buddhist education in SMK metta maitreya has been well performed based on the potential of students, measured from online learning in New Normal, according to the achievement of academic year 2021-2022, accountancy and computer engineering students which are 195 people acquired an average of 92, above minimum minimum criteria (KKM) 75, Whereas the aspect of development based on a well-defined 3.6-3.7 numerical range (B), it means that students have understood the moral aspects of accuracy, moral feeling, and action. According to dictates no.22 to 2016 concerning the standards of primary and secondary education processes. Second; Implementation of online learning in the new normal (new habits) modeling altruism approaches, teachers motivate and facilitate learning, to find a practical model that consolidate the normal role of learning in the new normal during pandemic, it also strengthens the passion to learn Buddhist Education in SMK metta maitreya which has done with great level of effectiveness in the school.